Genetic diversity analysis of local upland rice cultivars (Oryza sativa L.) from north provinces of Vietnam - Lan, Nguyen Thi Ngoc; Thanh Thanh, Nguyen Vu; Mau, Chu Hoang; Khanh, Nguyen Nhu (Academia Journal of Biology, 2012)
Genetic diversity of twenty five local upland rice cultivars (Oryza sativa L.) from 9 provinces of North in Vietnam was investigated at the morphologic grain characters and DNA levels. Results on classification of variety group of 25 local upland rice varieties indicated that there are fifteen Japonica subspecies and ten Indica subspecies. Analyzing principle components of ten grain characters include grain length, grain width, grain length/width ratio, 100-grain weight, awning, awn color, lemma and palea color, coat seed color, chalkiness of endosperm, endosperm type and variety group showed that the 100-grain weight and grain width were two main characters separated cultivars into four groups: small-large seeds, small-narrow seeds, big - narrow seeds, big - large seeds. To determine the genetic relationships among rice cultivars, we used the randomly amplified polymorphic DNA (RAPD) method. In the total five hundred of the polymerase chain reaction (PCR) with twenty random primers, 2431 DNA fragments were produced and genetic diversity index (HRAPD) was 47.46%. The coefficients of dissimilarity among upland rice cultivars were calculated between 8-21%.